Synthesis And In Vitro Biological Evaluation Of Metal Complexes Containing 2-Aminothiazole - Aditay Kumar; Mohd Hussain; Mamta khatak; Mohit Verma; Mohd Isfaq; Sudhir kaushik; Mahesh Kumar (Revista Electronica de Veterinaria, 2024)
In the present study, Schiff bases and metal complexes containing 2-aminothiazole have been synthesized and characterized by physicochemical and spectral means. Broth dilution assay (96 well microtiter plate method) was used to evaluate antimicrobial activity of the synthesized compounds against Gram positive bacteria (B. subtilis), Gram negative bacteria (E. coli) and fungal species (A. niger and A. terreus) using cefadroxil (antibacterial) and fluconazole (antifungal) as standard drugs. Among the synthesized derivatives, Schiff base EVL1 showed good activity against A. niger, A. terreus, B. subtilis (MICan,at,bs = 3.12 µg/ml). Complex MV1 showed good antifungal activity against A. niger (MICan = 1.56 µg/ml) similarly complex MV1 showed significant activity against E. coli, B. subtilis and A. terreus (MICec,bs,at = 3.12 µ/ml) and MV5 against A. niger (MICan = 1.56 µ/ml). Antioxidant (DPPH assay) 1,1-Diphenyl-2-picrylhydrazyl assay activity of the synthesized derivatives was determined using weight loss method. Schiff base MV1 showed excellent antioxidant activity (IC50 = 46.56).